Konflikt eller konsensus? : Kriminalpolitiken och riksdagen, 1946-1965 - Lexbro, Louise (Nordisk Tidsskrift for Kriminalvidenskab, 2000)
This article deals with the Swedish parliamentary debate on criminal policy during the period 1946-1965. The purpose of the study is to demonstrate the extent to which these debates were characterised by political cooperation as opposed to party antagonism. The study shows that the debate was defensive, limited, and generally cooperative. Only a few politicians took an active part in the debate in the parliament. Where conflicts did occur, both in the theoretical realm and in decision-making, there were not between political parties but rather between expert jurists. The results of the study show that criminal policy during this 20 year period was not a major political issue despite sharp, concurrent increases in Swedish crime rates.